KEPEMILIKAN SILANG SAHAM PT. INDOSAT DAN PT. TELKOMSEL OLEH TEMASEK HOLDING COMPANY - Lucianus Budi Kagramanto (Fakultas Hukum Universitas Gadjah Mada, 2008)
On Nopember 19, 2007, Commission For The Supervision Of Business Competition (KPPU) has been expelled a verdict No. 07/KPPU-L/2007 about infringement of Act No. 5, 1999 performed by Temasek Holdings. The form of infringement performed by Temasek Holdings is a stock cross ownership on PT. Indosat Tbk and PT. Telkomsel through its two subsidiaries company, namely STT and SingTel. Temasek Holdings is also accused on price fixing, double occupation, and also performing the monopoly in telecommunication, especially on cellular telephone. For the infringement, Temasek Holdings was sanctioned a fine and for the verdict, Temasek Holdings may propose a rejection to District Court of Jakarta. Other parties wish that the Court has objectivity and based on the business competition law in Indonesia. For the KPPU and Temasek Holdings still have a chance to propose an appeal to Supreme Court, if one are won by the District Court of Jakarta.